Pengembangan Lembar Kerja Siswa (LKS) pada Mata Pelajaran Matematika Materi Pecahan Kelas IV Sekolah Dasar - Nurmawati, Sri; Ain, Siti Quratul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This development research was carried out based on the teacher's difficulty in presenting interesting student worksheets (LKS), this is evidenced by the incompleteness and interestingness of other teaching materials such as worksheets that can help students understand the material. This study aims to test the feasibility of LKS in mathematics subjects with the content of fractions in fourth-grade elementary school. This research is development research using the ADDIE model. The data collected in this study are quantitative data and qualitative data. The methods used to collect data are observation, interviews, and questionnaires. The subjects involved in this study were 1 design expert, 1 material expert and 1 linguist, 1 teacher, and 6 students. The data analysis technique used is quantitative and qualitative descriptive data analysis techniques. The results showed that the feasibility of the LKS from the aspects of design, material, and language obtained an average score of 93.13% by category. Then the analysis of the fourth-grade teacher's response questionnaire to the LKS obtained an average of 86.91% with the